2019
DOI: 10.1111/nyas.14094
|View full text |Cite
|
Sign up to set email alerts
|

The expanding functional roles and signaling mechanisms of adhesion G protein–coupled receptors

Abstract: The adhesion class of G protein–coupled receptors (GPCRs) is the second largest family of GPCRs (33 members in humans). Adhesion GPCRs (aGPCRs) are defined by a large extracellular N‐terminal region that is linked to a C‐terminal seven transmembrane (7TM) domain via a GPCR‐autoproteolysis inducing (GAIN) domain containing a GPCR proteolytic site (GPS). Most aGPCRs undergo autoproteolysis at the GPS motif, but the cleaved fragments stay closely associated, with the N‐terminal fragment (NTF) bound to the 7TM of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 112 publications
(163 reference statements)
0
18
0
Order By: Relevance
“…Adhesion-GPCRs characteristically contain large extracellular sequences with multiple potential ligand-binding domains and a canonical GAIN domain that is coupled to the 7transmembrane region module characteristic of GPCRs (reviewed in Vizurraga et al, 2020;Morgan et al, 2019;Folts et al, 2019;Purcell and Hall, 2018). Most adhesion-GPCRs additionally have a long cytoplasmic region.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion-GPCRs characteristically contain large extracellular sequences with multiple potential ligand-binding domains and a canonical GAIN domain that is coupled to the 7transmembrane region module characteristic of GPCRs (reviewed in Vizurraga et al, 2020;Morgan et al, 2019;Folts et al, 2019;Purcell and Hall, 2018). Most adhesion-GPCRs additionally have a long cytoplasmic region.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion-GPCRs characteristically contain large extracellular sequences with multiple potential ligand-binding domains and a canonical GAIN domain that is coupled to the 7-transmembrane region module characteristic of GPCRs (reviewed in Vizurraga et al, 2020; Morgan et al, 2019; Folts et al, 2019; Purcell and Hall, 2018). Most adhesion-GPCRs additionally have a long cytoplasmic region.…”
Section: Introductionmentioning
confidence: 99%
“…This in combination with recent advances in our understanding of GPCR structures has formed a strong foundation for rational drug design to target this largest superfamily of surface receptors 4,5 . Recent genomic and model organism studies have revealed the versatile roles that the adhesion GPCRs (aGPCRs), the second-largest family of GPCRs, play in endocrine, nervous and immune systems 6 . aGPCRs have structural differences with other classes of GPCRs, namely autoproteolysis at a GPCR proteolysis site (GPS) and formation of a two-segmented receptor with a large N-terminal fragment (NTF) and a C-terminal fragment (CTF).…”
Section: Introductionmentioning
confidence: 99%